Систематизація трансформаторно-ключових виконавчих структур перетворювачів напруги з ключовими елементами у колі силового струму - Липківський, К.О. (Технічна електродинаміка, 2011)
Transformer switching executive structures are known to have a variety of topological implementations, and their systematization is needed. It is proposed that the main classification criterion be the location of switching elements. The structures are divided by this criterion in two classes, one with switching elements located in the load current circuit, and the other with switching elements withdrawn from the load current circuit. The first class is systemized and divided into seven groups. A method of a topological conversion for electrical circuits with the finite set of sections of the transforming element and the finite set of swithching elements is devised. This method makes it possible to synthesize structures with increased usage of switching and transforming elements.